2004
DOI: 10.1074/jbc.m312856200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Yeast MRF1 Gene Encoding Mitochondrial Release Factor Inhibit Translation on Mitochondrial Ribosomes

Abstract: Although the control of mitochondrial translation in the yeast Saccharomyces cerevisiae has been studied extensively, the mechanism of termination remains obscure. Ten mutations isolated in a genetic screen for read-through of premature stop codons in mitochondrial genes were localized in the chromosomal gene encoding the mitochondrial release factor mRF1. The mrf1-13 and mrf1-780 mutant genes, in contrast to other alleles, caused a non-respiratory phenotype that correlated with decreased expression of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Although Mtq1p modifies the Mrf1p, the protein that is essential for mitochondrial function (27), the mtq1-⌬ mutant had no significant phenotypes on solid media (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Mtq1p modifies the Mrf1p, the protein that is essential for mitochondrial function (27), the mtq1-⌬ mutant had no significant phenotypes on solid media (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The only release factor that acts at the translation termination stop codons in mitochondria is mRF1 (24,26). In the yeast S. cerevisiae, the MRF1 gene encodes a protein more similar to the prokaryotic RF1 than to RF2, and the MRF1 gene is required for proper translation in mitochondria (27). Mrf1p recognizes only the termination codons UAA and UAG on mitochondrial and bacterial ribosomes (25), the same codons recognized by RF1.…”
mentioning
confidence: 99%
“…However, termination of translation and recycling show stunning deviations from the bacterial pathway [3841]. For example, mammalian mitochondria utilize only one release factor, mtRF1a [42], to decode all stop codons [43, 44]. …”
Section: Introductionmentioning
confidence: 99%
“…We also show an interesting interaction between the mitochondrial mim3-1 and the nuclear nam3-1 suppressors, both of which have the same action spectrum on mitochondrial mutations: nam3-1 abolishes the suppressor effect when present with mim3-1 in the same haploid cell. We discuss these results in the light of the nature of Nam3, identified by 1 as the yeast mitochondrial translation release factor. A hypothetical mechanism of suppression by "ribosome shifting" is also discussed in view of the nature of mutations suppressed and not suppressed.…”
mentioning
confidence: 87%
“…The MSU1 mutation suppresses only ochre mutations and has occurred at the base of the so called "530-loop" in the 15S rRNA 11. A few years ago, it was shown that the Nam3 protein corresponds to the release factor Mrf1 and the identification of the nam3-1 suppressor mutation was also reported 1.…”
Section: Introductionmentioning
confidence: 99%